Veracities of teaching listening in Nepal - Ghimire, Nanibabu (Journal of NELTA, 2019)
This study explores realities, problems and their solutions of teaching listening in English in secondary level education in Nepal. As it is a narrative inquiry, I chose three English teachers and six students from three different secondary level community schools of Kamalamai Municipality of Sindhuli district, Nepal as the participants of the study using purposive sampling procedure. The findings demonstrated that the listening skill is the neglected skill in our school education. The teachers do not pay much more attention to teach this skill in our community school by thinking teaching listening is not important for examination purpose. There is scarcity of audio-visual devices, the classroom is not techno-friendly, teachers are not dedicated and trained, monitoring strategies of concerned authority is not effective for teaching listening. Recommended solutions include - the students should be proactive and the school administration has to be responsible for making availability of listening equipment and materials. Similarly, the teachers should use various interactive and cooperative activities such as role-play, pair work, group work and communication games using authentic materials such as English films, favourite songs, funny short stories, some exciting programmes on radio, TV or the internet for the effectual teaching of listening.